Determination of the water gap and the germination ecology of Adenanthera pavonina (Fabaceae, Mimosoideae); the adaptive role of physical dormancy in mimetic seeds. Issue 5 (23rd August 2018) - Jaganathan, Ganesh K; Yule, Kirsty J; Biddick, Matthew
Abstract: Dormancy caused by impermeable seed coats, i.e. physical dormancy (PY), regulates the timing of seed germination in species of several genera belonging to 18 angiosperm families. Physical dormancy also occurs in some mimetic species whose seeds mimic brightly coloured, fleshy fruits or arilled seeds. However, the conditions that break dormancy, as well as the location of water gaps in mimetic seeds, remain unclear. Here, we investigated the adaptive role of impermeable coats in the mimetic seeds of Adenanthera pavonina (Fabaceae: Mimosoideae). Specifically, we explored: (i) the conditions that break PY; (ii) the location of the primary water gap that forms during dormancy break; and (iii) the effect of seasonal temperature regimes on seed germination. Seeds were subjected to hot-water treatment, rapid temperature fluctuations and storage at temperatures mimicking summer and autumn conditions. Seed coat anatomy and water-gap regions were characterized using scanning electron microscopy (SEM) and light microscopy. Seeds were artificially buried in the field at 3 and 7 cm depths and exhumed every 6 months for 2 years to monitor germination. Adenanthera pavonina had impermeable seed coats, and thus PY. Seeds treated with hot water and exposed to summer–autumn temperature regimes broke dormancy. Water entered only through the lens (Type-II simple) due to dislodgement of the palisade layer. Seeds buried at 3 cm depth had significantly higher germination than those buried at 7 cm depth, with germination primarily occurring in autumn. Seeds required high summer temperatures followed by moderate autumn temperatures to become permeable to water and germinate in the field during the wet season. We conclude that the impermeable seed coat of A. pavonina is an adaptation that synchronizes germination with the growing season. Abstract : Several hypotheses have been described for the evolution of impermeable seed coat, i.e. physical dormancy (PY) in mimetic-seeded species. However, no attempts have been made to understand the importance of dormancy in controlling germination timing in mimetic species. Thus, in this study, we investigated this knowledge gap using Adenanthera pavonina and found impermeable seed coats are indeed a form of dormancy and evolved to control germination timing in mimetic species, although future studies on other species are required.